Effect of Nickel and Cobalt on Methanogenic Enrichment Cultures and Role of Biogenic Sulfide in Metal Toxicity Attenuation - Paulo, Lara M.; Ramiro-Garcia, Javier; van Mourik, Simon; Stams, Alfons J. M.; Sousa, Diana Z. (Frontiers in Microbiology, 2017)
Metals play an important role in microbial metabolism by acting as cofactors for many enzymes. Supplementation of biological processes with metals may result in improved performance, but high metal concentrations are often toxic to microorganisms. In this work, methanogenic enrichment cultures growing on H2/CO2 or acetate were supplemented with trace concentrations of nickel (Ni) and cobalt (Co), but no significant increase in methane production was observed in most of the tested conditions. However, high concentrations of these metals were detrimental to methanogenic activity of the cultures. Cumulative methane production (after 6 days of incubation) from H2/CO2 was 40% lower in the presence of 8 mM of Ni or 30 mM of Co, compared to controls without metal supplementation. When acetate was used as substrate, cumulative methane production was also reduced: by 18% with 8 mM of Ni and by 53% with 30 mM of Co (after 6 days of incubation). Metal precipitation with sulphide was further tested as a possible method to alleviate metal toxicity. Anaerobic sludge was incubated with Co (30 mM) and Ni (8 mM) in the presence of sulphate or sulphide. The addition of sulphide helped to mitigate the toxic effect of the metals. Methane production from H2/CO2 was negatively affected in the presence of sulphate, possibly due to competition of hydrogenotrophic methanogens by sulphate-reducing bacteria. However, in the enrichment cultures growing on acetate, biogenically produced sulphide had a positive effect and more methane was produced in these incubations than in similar assays without sulphate addition. The outcome of competition between methanogens and sulphate-reducing bacteria is a determinant factor for the success of using biogenic sulphide as detoxification method.